Preparing Grade R learners for formal schooling in the multi-grade classroom in Lesotho - Ntsinyi, Makorina Pearl (University of the Free State, 2023)
The transition from pre-school to formal schooling is a critical juncture in a child's educational journey. This study examined the challenges and strategies involved in preparing Grade R learners for formal schooling, particularly within the context of multi-grade classrooms in Lesotho. Most Early Childhood Education pre-schools in Lesotho practise multi-grade teaching, where one teacher teaches different ages and multiple grade levels in one classroom. Pre-school teachers in Lesotho are not equipped to teach in a multi-grade classroom, though it is a common practice in Lesotho pre-schools. This study aimed to investigate the lived experiences and challenges faced by pre-school teachers in preparing Grade R learners for school readiness in a multi-grade classroom. The study considered different teaching strategies such as planning, grouping, classroom organisation, classroom management and assessment, adopted by pre-school teachers. It also identified challenges including the lack of training and curriculum guidance. Four pre-school teachers from different schools within Maseru Urban participated in the study. The qualitative research approach located within the contours of the interpretivist paradigm were chosen for this study. Themes were developed through thematic analysis. They explore strategies and challenges of pre-school teachers in preparing Grade R learners for formal school readiness. Vygotsky’s socio-cultural theory formed the theoretical framework underpinning this study. The findings revealed that pre-school teachers lacked sufficient training and curriculum advice in teaching multi-grade classrooms as they still used mono-grade curricula. The study also found that pre-school teachers adopted different teaching strategies they found essential and effective in preparing Grade R learners for formal school readiness. Training for multi-grade teaching needs to be prioritised as it is the popular teaching arrangement in Lesotho.
Dissertation (M.Ed.(Early Childhood Development))--University of the Free State, 2023
Keywords: Multi-grade teaching; Grade R school readiness; Formal schooling; Transition from pre-school; Strategies; Socio-cultural theory